Proton ordering model of phase transitions in hydrogen bonded ferrielectric type systems: the GPI crystal - Stasyuk, I.; Czapla, Z.; Dacko, S.; Velychko, O. (Condensed Matter Physics, 2003)
A microscopic model based on the consideration of the proton ordering is proposed for describing the H-bonded ferroelectric crystalline systems with a complex structure of the hydrogen bond network. The model has been used for the investigation of thermodynamics and dielectric properties of the GPI crystal. The symmetry analysis of the order parameters responsible for the mixed (ferro- and antiferroelectric) nature of ordering is performed within the model. The phase transition into the ferroelectric state is described. Changes in the dielectric susceptibility of the crystal are studied in the presence of the transverse external electric field acting along the c - axis. The results of measurements of temperature and field dependences of dielectric permittivity ε'c in the paraelectric phase are presented. The microscopic mechanism of the observed effects is discussed based on the comparison of theoretical results and experimental data. A conclusion is made about the significant role of the ionic groups connected by hydrogen bonds in the charge transfer. So they make an important contribution into the polarizability of the GPI crystal along the direction of H-bonded chains.